Ultimate Black Panther. Vol. 1, Peace and war - Hill, Bryan Edward (Marvel Worldwide, Inc., 2024)
"In the wake of ULTIMATE INVASION, Khonshu and Ra -- the force known together as Moon Knight -- are seeking to expand their brutal control of the continent of Africa. In response, the lone bulwark against them, the isolated nation of Wakanda, will send forth its champion...its king...the Black Panther! After Moon Knight's forces attack the stronghold of Wakanda, T'Challa can no longer resist Shuri and the Dora Milaje's calls to action. Grieving and enraged, the Panther demands to know who has been leaking information about Wakanda to their enemy...and the source shocks him to his core. Plus: A prophecy about T'Challa threatens to upend the war -- and all of Wakandan life!"--